2017
DOI: 10.1089/zeb.2017.1442
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Taking During Feeding: Between- and Within-Population Variation and Repeatability Across Contexts Among Wild Zebrafish

Abstract: Behavioral responses are shaped by a complex interplay of extrinsic factors, such as predation and flow conditions, and intrinsic properties such as metabolic state. We investigated variations in boldness among four populations of zebrafish collected from widely varying habitat conditions across India. We measured feeding latencies of fish in four contexts: in a novel environment; in an environment with refuge and predators; in the presence of a shoal; and in the presence of a shoal and predators. The populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 65 publications
7
49
1
Order By: Relevance
“…Time spent in the center zone showed the greatest variability across weeks compared to stationary time and swimming speed. While several studies have found sex-specific behavioral variation of mating and aggressive behaviors 46,47,60 , we did not observe any sex differences in exploratory behavior.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Time spent in the center zone showed the greatest variability across weeks compared to stationary time and swimming speed. While several studies have found sex-specific behavioral variation of mating and aggressive behaviors 46,47,60 , we did not observe any sex differences in exploratory behavior.…”
Section: Discussioncontrasting
confidence: 99%
“…These studies suggest that selection can influence expression of repeatability and reliability by potentially placing survival costs on individuals. Predation has frequently been identified as one of the strongest ecological pressures that can influence the repeatability and reliability of animal behavior 11,16,47 . We speculate that by selecting for an ecologically relevant behavioral response to a stressor in the HSB and LSB lines within the lab, it may have been simulating selection of behavioral responses to predation in the wild.…”
Section: Discussionmentioning
confidence: 99%
“…; Roy et al. ). However, the sociability trait was more tightly correlated to total activity than to risky activity, suggesting that this interpretation is unlikely.…”
Section: Discussionmentioning
confidence: 98%
“…While poeciliid Brachyraphis episcopi populations from high-predation regimes were more exploratory and active than low-predation populations [ 12 ], three-spined sticklebacks Gasterosteus aculeatus from high-predation habitats were less bold and active than those from low-predation habitats [ 8 ]. In our previous study, we found fish from high-predation habitats to be bolder than fish from low-predation habitats [ 13 ]. Recent studies investigating the role of different selective forces in determining temperament traits indicate that the direction of correlations between behaviours can actually vary across populations [ 1 ].…”
Section: Introductionmentioning
confidence: 99%